2006
DOI: 10.1249/00005768-200605001-01401
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Study Examination of Physiological Variables Associated with Improved Endurance Performance with Carbohydrate/Protein Administration

Abstract: PURPOSE: Previous studies from our laboratory reported improvements in endurance performance when athletes consumed carbohydrate/protein (CHO+P) beverages or gels compared to carbohydrate-only (CHO) treatments. However, relatively small sample sizes in these studies precluded the ability to examine correlations between physiological variables that may have been associated with performance benefits. Therefore, the purpose of this study was to examine data across multiple studies to determine if improvements in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thus, the authors concluded that the combined data showed significant improvements in endurance performance with carbohydrate/protein versus carbohydrate supplementation. 64 Effect on Carbohydrate/Protein Supplementation on Muscle Damage and Soreness. In 2 investigations previously described by Saunders and colleagues, carbohydrate/protein supplements ingested during endurance exercise resulted in longer times to exhaustion compared to carbohydrate alone, and also demonstrated lower levels of plasma creatine kinase (CPK) in the carbohydrate/protein treatment compared to carbohydrate only.…”
Section: Carbohydrate/proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the authors concluded that the combined data showed significant improvements in endurance performance with carbohydrate/protein versus carbohydrate supplementation. 64 Effect on Carbohydrate/Protein Supplementation on Muscle Damage and Soreness. In 2 investigations previously described by Saunders and colleagues, carbohydrate/protein supplements ingested during endurance exercise resulted in longer times to exhaustion compared to carbohydrate alone, and also demonstrated lower levels of plasma creatine kinase (CPK) in the carbohydrate/protein treatment compared to carbohydrate only.…”
Section: Carbohydrate/proteinmentioning
confidence: 99%
“…63 Given the conflicting findings across studies, and the relatively small sample sizes used in many of the investigations, Saunders et al examined data across multiple studies to determine if performance was in fact related to changes in physiological measures during exercise. 64 To accomplish this, 38 subjects were combined from 3 studies in which cyclists performed rides to exhaustion at 75% V o 2 peak. In each study analyzed, cyclists received carbohydrate (7.3%) or carbohydrate/protein (7.3% + 1.8%) every 15 minutes during exercise.…”
Section: Nutrient Timingmentioning
confidence: 99%
See 1 more Smart Citation